Penerapan model think pair share dengan media audio untuk meningkatkan keterampilan menyimak cerita rakyat kelas iv sekolah dasar - Meilani, Atika Devi; Hartono, Hartono; Sularmi, Sularmi (Didaktika Dwija Indria, 2019)
Abstract. This research aims is to improve the students listening of folklore skill with model Think Pair Share and media audio in 4th grade students of SDN Selomulyo Sleman academic year 2018/2019. This research is a classroom action research conducted three cycles. Each cycle consist of four stage. The research data was collected through interviews, observation, test, and documentation. Data validity are using triangulation of source and triangulation of technique. Data analysis technique used was descriptive of comparative and interactive model. The researcher used five indicator to know the level of students listening of folklore skill. That all instrinsic elements, text comprehension, main problem, text organizaion, and problem solving. The results shows that classical completeness on pre-action is 7,69%, increase on cycle I by 43,21% ,increase on cycle II by 69,23% , and increase again in cycle III by 88,46%. Based on the result, the conclusion is the application of model Think Pair Share and media audio can improve the students listening of folklore skill on 4th grade students of SDN Selomulyo Sleman academic year 2018/2019.Keywords : Think Pair Share, media audio, students listening of folklore skil, elementary school